HOW THE FAMILY 500+ PROGRAM FACILITATES SOCIAL INVESTMENTS? - Grewinski, Miroslaw; Lizut, Joanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In 2016, the Polish government considered necessary to undertake public actions aimed at influencing the structure of population and the course of demographic processes. At the same time, public policieshave been established to respond to the expectations of citizens resulting from the new population structure and societalchanges. This article describes the Polish Family 500+ programafter 2 years of its implementation. The Family 500+ program is not only a legislative means to increase the birth rate, but also representsa new paradigm in social policy, which would ensure ahigh level of social capital to future generations.